Is foreign direct investment globalization‐induced or a myth? A tale of Africa - Aluko, Olufemi Adewale; Chen, George S.; Opoku, Eric Evans Osei (John Wiley & Sons, Ltd., 2021)
Foreign direct investment (FDI) provides many African countries an important source of capital inflow. Despite notable improvements in these capital-scarce countries' economic, political, and social conditions, foreign investors have not considered them viable host locations. Since FDI brings enormous spillovers to its host, some countries have recently institutionalized globalization as the catalyst for reversing the trend. Against this backdrop, we examine the FDI–globalization nexus across 47 African countries for the 1996–2016 period. Using the augmented mean group estimator, the results suggest that FDI in Africa is indeed globalization-induced. Moreover, we find this positive nexus to be driven by the economic dimension of globalization. Overall, we demonstrate the potential of globalization in stimulating an FDI boom in Africa.